Visual Cues Generated During Action Facilitate 14-Month-Old Infants' Mental Rotation. Issue 3 (26th May 2016) - Antrilli, Nick K.; Wang, Su-hua
Abstract : Although action experience has been shown to enhance the development of spatial cognition, the mechanism underlying the effects of action is still unclear. The present research examined the role of visual cues generated during action in promoting infants' mental rotation. We sought to clarify the underlying mechanism by decoupling different aspects of action experience and choosing to manipulate the visual aspect while holding other aspects constant. Fourteen-month-old infants were given opportunities to rotate a cylinder placed on a turntable; the cylinder was decorated with vertical or horizontal stripes. If the effects of action hinge on the quality of visual cues generated during action, infants should benefit more from rotating the cylinder with vertical stripes as they generate richer cues when each stripe moves laterally with the cylinder. As predicted, the infants in the vertical-stripe condition looked significantly longer at an improbable outcome than at a probable outcome of a hidden-rotation event, whereas those in the horizontal-stripe condition looked about equally at the 2 outcomes. The results suggest that the effects of action on mental rotation are derived not from motor experience alone, but from integrating motor and visual experiences.